COMPUTER SUPPORT OF ERGONOMIC ANALYSIS OF WORKING CONDITIONS AT WORKSTATIONS - Damian KOLNY; Dawid KURCZYK; Józef MATUSZEK (Applied Computer Science, 2019)
The article shows issues of using computer-aided technologies for ergono-mic analysis at worksplaces using a dedicated tool in the Delmia environment. The scope of the ergonomic evaluation has been limited to the analysis of RULA and NIOSH, the data needed for it was gathered on the basis of observation, interview and task analysis. The results of the research showed the strenous nature of the work, therefore improvements within undertaken workplace area were proposed and re-analyzed. The obtained results proved reduction of strenousness, which was the basis for the practical implemen-tation of the proposed changes.